Transplacental Transfer of Primaquine and Neurobehavioral Development of Prenatally Exposed Rats - Klaus M. Becker; Lorenna Rosa; Manoella S. B. Fernandes; Rosangela R. de Carvalho; Ana Cecilia X. De-Oliveira; Davyson L. Moreira; Francisco J. R. Paumgartten (Journal of Toxicology)
Primaquine (PQ) not only eliminates P. falciparum gametocytes but also kills liver dormant forms of P. vivax and P. ovale. Owing to these unique therapeutic properties, it is an essential drug. Although PQ has been used for over 70 years, its toxicological database has gaps such as the absence of studies on its reproductive and developmental toxicity and kinetics in pregnancy. This study investigated the transplacental transfer of PQ and the effects of intrauterine exposure on the postnatal growth, survival, and neurobehavioral development of the offspring. PQ kinetics and transplacental transfer were investigated in rats treated orally (40 mg.kg·bw−1) on gestation day (GD) 21. PQ was analyzed by high-performance liquid chromatography with diode array ultraviolet detection. To evaluate effects of intrauterine exposure on postnatal development, dams were treated orally with PQ (20 mg.kg·bw−1·d−1) or water (controls) on GD 0–21. Postnatal survival, body weight gain, somatic maturation, and reflex acquisition were evaluated. The open field test (OF) was conducted on PND 25. PQ concentration in the fetal plasma was nearly half that in maternal plasma. Except for increase in pregnancy loss, no effects of PQ were noted at term pregnancy and first days of life. Prenatal PQ did not affect postnatal weight gain nor did it impair somatic and neurologic development of the offspring. Pups born to PQ-treated dams showed reduced exploration and enhanced emotionality in the OF. PQ given in pregnancy, at doses greater than those recommended for malaria therapy, may affect pup postnatal survival and emotional behavior.